Growing Nuclearization of the Indian Ocean and its Implications For South Asian Stability - Mr. Muhammad Sarmad Zia (CISS Insight Journal, 2017)
The paradigm of security in the Indian Ocean Region (IOR) is going through a major transformation. It is a beginning of a new and unprecedented era in this part of the world. The geopolitical and economic orientation is shifting from Atlantic to Indian and Pacific Oceans as major powers such as China and United States seek to exert their influence in the region. China’s major trade and hydrocarbon shipments pass through the Indian Ocean which makes it an important area for China to ensure security of trade. The littoral states of Indian Ocean are also vying to push their weight. The enormous volume of global maritime trade that passes through it also signifies its increasing importance in the world now. A report from 2015 shows that seventy percent of world’s trade by volume, amounting to 777 Billion dollars, passes through the Indian Ocean.1 With the advent of naval powers with nuclear submarines and nuclear tipped ballistic and cruise missiles, the contours of strategic security are evolving in the IOR.